QUANTITATIVE DETERMINATION OF VITAMINS A, D3 AND E IN PREMIXES «MAUERVIT» AND «GRANDVITAM» BY ULTRA HPLC - A. V. Baklykov (Разработка и регистрация лекарственных средств, 2019)
A convenient method for analyzing the content of vitamins A, D3 and E in premixes has been developed (the tests were carried out using the example of the premixes «Mauervit» and «randvitam») using ultra HPLC. The necessary changes of the procedure have been made in comparison with the ones presented previously in GOST R 50928-96 due to the presence in the premix components hampering analysis (in particular, Tween 80). The developed procedure has been tested in terms of specificity, accuracy and precision. In addition, the possibility of using a simpler procedure for the analysis of vitamins extract, used as raw material for premix production, has been demonstrated.